Why humility is vital to effective humanitarian aid leadership: a review of the literature. Issue 4 (13th June 2021) - Wang, David C.; Hall, M. Elizabeth Lewis; Shannonhouse, Laura R.; Mize, Mary Chase Breedlove; Aten, Jamie D.; Davis, Edward B.; Van Tongeren, Daryl R.; Annan, Kent
Abstract : Organisational scientists are paying increasing attention to humility, following a larger trend in scholarship highlighting the relational and interdependent nature of leadership and business. A growing body of evidence identifies humility as vital to effective organisational leadership, facilitating positive organisational outcomes, such as lower voluntary turnover and greater follower job satisfaction. To date, research on the subject has focused on certain specific organisational contexts, including businesses, hospitals, and schools. This paper reviews the existing literature and explores why humility may be an especially important leader trait in international humanitarian aid organisations and relief work—a context that is not only uniquely challenging, but also one that would seemingly stand to benefit keenly from the quality. It argues that humility is essential for effective leadership because it is normative of good character, it is predictive of positive outcomes, and it corresponds to a genuine representation of the nature of humanitarian aid.